Critical discourse analysis of presidential candidates TV debates between Ebrahim Raisi and Abdolnaser Hemmati in Iran’s 2021 presidential election - Hamid Reza Rahro; Peyman Jebelli; Fatemeh Azimfard (Social Sciences and Humanities Open)
This study conducts a Critical Discourse Analysis of the televised presidential debates between Iranian candidates Ebrahim Raisi and Abdolnaser Hemmati. Utilizing linguistic devices from Teun A. Van Dijk's framework at both micro and macro levels, the paper examines the political discourse employed by the candidates. Analysis reveals that Raisi utilized more positive language compared to Hemmati, while Hemmati employed negative ironies four times more frequently than Raisi. Raisi's key propositions focused on supporting manufacturing, housing construction, transparency, anti-corruption efforts, jihadi management, and economic justice. Hemmati's key propositions included lifting sanctions, promoting social freedoms and women's empowerment, restructuring the economy, and navigating sanctions through joining the FATF.